Home Purchase Decision Support System Using the Brown-Gibson Method - Rita Frances (Jurnal Mandiri IT, 2021)
thesis. The application program was built by applying the Brown-Gibson method which is capable of measuring both qualitative and In making a decision to buy a house, a buyer will consider a variety of complex criteria, such as qualitative (non-numeric) and quantitative (numeric) criteria to get the best decision. To simplify the process, a home purchase decision-making application program was created in this quantitative criteria. The algorithms in the Brown-Gibson method used in this application program include: "Performance Measurement" to measure quantitative criteria, such as house selling price, land area, building area and number of bedrooms; “Pairwise Comparison” to measure qualitative criteria, such as architectural style, position of the building, proximity to the work environment, proximity to shopping centers, proximity to the educational environment, state of the home environment, building status, house certificate; and "Preference of Measurement" which combines the quantitative and qualitative criteria to produce a priority weight that can be accepted as a measurement result for each alternative house as a whole. The final result of this thesis is an application program that provides the highest value for an alternative home. The house that gets the highest score is an alternative house that has the most suitable specifications according to the criteria considered by the buyer. The house that gets the highest score is an alternative house that has the most suitable specifications according to the criteria considered by the buyer. the condition of the house environment, the status of the building, the certificate of the house; and "Preference of Measurement" which combines the quantitative and qualitative criteria to produce a priority weight that can be accepted as a measurement result for each alternative house as a whole. The final result of this thesis is an application program that provides the highest value for an alternative home. The house that gets the highest score is an alternative house that has the most suitable specifications according to the criteria considered by the buyer. and "Preference of Measurement" which combines the quantitative and qualitative criteria to produce a priority weight that can be accepted as a measurement result for each alternative house as a whole.